Long-Term Field Biochar Application for Rice Production: Effects on Soil Nutrient Supply, Carbon Sequestration, Crop Yield and Grain Minerals - Xu, Qiao; Wang, Ji; Liu, Qi; Chen, Zhe; Jin, Penghui; Du, Jiazhou; Fan, Jialu; Yin, Weiqin; Xie, Zubin; Wang, Xiaozhi (Agronomy (Basel), 2022)
Research is still under-represented for the long-term impacts of field biochar application on soil fertility, rice production and mineral nutrition and soil C sequestration. To investigate these effects, a field trial was established in the fall of 2010 with low (2.4 t ha−1), intermediate (6 t ha−1) and high (12 t ha−1) biochar doses. The biochar effect on soil nutrients is more pronounced in the surface soil and is dose dependent. In the surface soil, biochar application increased the availability of soil N, P and K. High dose decreased soil total Fe by 11.6% and Mn by 20.7%, leading to a slight but insignificant decrease in grain Fe and Mn concentration. The intermediate and high doses significantly increased the soil available Zn by 96.2% and 227.9% but did not affect the grain Zn concentration. Grain Cu concentration was significantly decreased by the intermediate (−19.6%) and high (−14.3%) dose of biochar. Biochar had a slight but insignificant boost on rice yield. Soil total C and N increased linearly with biochar application for the surface soil only where biochar was applied. In conclusion, with great soil C sequestration capacity, the long-term field return of biochar is beneficial for improving the soil macronutrient and Zn fertility, but caution is needed, as higher doses of biochar could potentially lead to a decrease in soil Fe and Mn and a reduction in grain Cu concentration.